Design and analysis of a broadband and miniaturized linear polarized converter based on non‐Foster metasurfaces. Issue 1 (27th August 2020) - Li, Fengxia; Chen, Haiyan; Zhou, Yang; Zhang, Li; Weng, Xiaolong; Xie, JianLiang; Deng, Longjiang
Abstract: A broadband highly efficient and miniaturized polarizing converter, employing non‐Foster metasurface composed of a single layer cut‐wire resonator is presented in microwave regime. Non‐Foster component are loaded to traditional dipole‐type linear polarized converter to further enhance the low frequency polarization conversion performance, comparing to the converter without non‐Foster component, it makes all resonant frequency points move to the lower frequency obviously. Simulated results show that the cross‐polarization conversion is greater than 80% in the relative bandwidth of 143.9% for normal incident waves. Moreover, the period of the proposed polarized converter is less than 0.09 wavelength of the lowest operation resonant frequency, which indicates that the converter has the characteristic of miniaturization. By combining the transmission line and equivalent circuit theory, the physical underpinnings of this converter are further discussed, based on this analysis, the corresponding resonant frequencies are calculated as 4.2 GHz, 12.7 GHz, and 26.3 GHz, respectively. The simulated and numeral results are basically consistent. This method can be applied to the design of low frequency polarization structures.